Utilization Chart of Account For Effectiveness Company Cash Mapping On Web Based Accounting Online System 2.0 - Suryana, Endang; Syafnidawati, Syafnidawati; Aryani, Diah (APTISI Transactions on Management (ATM), 2017)
In a company, the accounting system is very important, because it contains financial information that can be used to make a decision. Currently already developed online web-based accounting, where the accounting system can be used anytime and anywhere with an internet connection. An accountant is someone who has an important role in the success of financial processing company. Where, to facilitate the processing process, the accountant must be able to perform the company's cash mapping. By grouping into multiple accounts will facilitate the process of financial information delivery. The data of all transactions will be entered into accounts that have been made previously. And if the accounts that have been used in the year are not reused, then the accountant can delete the account, then add a list of new accounts. However, if the account is still reused, the accountant can also archive the account, so the data will not be deleted, but only archived or hidden. Thus, the menu chart of accounts in WBAOS 2.0 (Web Based Accounting Online System) can facilitate the recording of corporate cash mappings. Keywords​: WBAOS, Chart of Account, and cash mapping